2012
DOI: 10.1074/jbc.m112.371203
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of HuR Protein during Alphavirus Infection Is Associated with HuR Relocalization to the Cytoplasm

Abstract: Background: Sindbis virus RNAs bind the cellular HuR protein and cause its relocalization to the cytoplasm. Results: HuR relocalization occurs with other alphaviruses but not with several unrelated RNA viruses. It is associated with altered protein phosphorylation. Conclusion: HuR relocalization is alphavirus-selective and appears to be distinct from other types of HuR shuttling. Significance: This has potential therapeutic and diagnostic implications for alphavirus infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 40 publications
1
57
1
Order By: Relevance
“…HuR relocalization has been observed upon infection with alphaviruses but not dengue virus which, like HCV, belongs to the Flaviviridae family (46). Hence, it may not be a general phenomenon observed in all members of the Flaviviridae family.…”
Section: Discussionmentioning
confidence: 95%
“…HuR relocalization has been observed upon infection with alphaviruses but not dengue virus which, like HCV, belongs to the Flaviviridae family (46). Hence, it may not be a general phenomenon observed in all members of the Flaviviridae family.…”
Section: Discussionmentioning
confidence: 95%
“…by p38, dictates their activity. Modulation of ARE interacting proteins has been noted as a mechanism by which viruses influence inflammatory responses in host cells [32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…First, the 3′UTRs in both alphaviruses [15]–[18] and flaviviruses [19] interact with cellular proteins (in both mosquito and mammalian cells) to directly or indirectly facilitate genome replication. It has been observed that several alphaviruses usurp the cellular HuR protein, which enhances mRNA stability and therefore inhibits viral RNA decay [16][18]. Additionally, arboviral 3′UTRs can encode microRNAs (miRNAs, such as observed in West Nile virus) which regulate cellular gene expression to enhance viral replication [20].…”
Section: Introductionmentioning
confidence: 99%